Ideological Character, for Example “Jamshid Khan Mam’s Novel by Bakhtiyar Ali - Rebwar Kareem Sleman; Tanya Asaad Mohammed Salh (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
This research is entitled " Ideological Character, for example "Jamshid khan Mam's novel by Bakhtiyar Ali. It is an attempt to show and lighting important Topic, name the ideological dimension of the novel, to capture the results of the ideological character. It seems that not much has been done in Kurdish literature, specially ideology in novel. That dimension is less talked about than others dimension. The novel like a modern literary genre, is not empty in ideology, and the character conveys the novelist 's philosophy and Idea to the reader.